PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA DALAM STRATEGIC SUPPLY RELATIONSHIP DENGAN KERJASAMA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Apotek Di Kota Ambon) - Salhuteru, Fentje (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
This study aimed to examine the effect on the performanceof management control systems in strategic supply relationship withthe co-operation as an intervening variable in a pharmacy in the cityof Ambon. These results indicate that the Performance MeasurementSystem a significant effect on performance in the Strategic SupplyRelationship (SSRs). Furthermore, significant effect on theSocialization Process Performance In Strategic Supply Relationship(SSRs). Similarly Performance Measurement System significantlyinfluence Cooperation. Then the process of socialization significanteffect on cooperation. Cooperation significant effect on performancein the Strategic Supply Relationship (SSRs). The performancemeasurement system did not significantly affect the performanceSSRs through cooperation as an intervening variable. Similarly, theprocess of socialization significant effect on the performance SSRsthrough cooperation as an intervening variable.Key word: Strategic Supply Relationship, PerformanceMeasurement System, Socialization Process,Performance